2017
DOI: 10.1111/asj.12782
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a protected inclusion of organic acids and essential oils as antibiotic growth promoter alternative on growth performance, intestinal morphology and gut microflora in broilers

Abstract: This experiment was conducted to investigate the effects of protected essential oils and organic acids mixture on poultry feeding. A total of 450 1-day-old Cobb 500 chicks were randomly allotted into three treatments with six replicates. Birds were offered a basal diet (C), basal diet with 0.15 g/kg enramycin premix (A) and basal diet with 0.30 g/kg protected essential oils and organic acids mixture product (P). The results showed that protected essential oils and organic acids mixture supplementation reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
58
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 37 publications
12
58
0
1
Order By: Relevance
“…Our results indicated that feeding with BLJ could positively improve FCR in broilers. Consistent with our findings, several recent studies documented that EOA improved the growth performance and/or feed utilization in broilers [47,48] and turkeys [49]. Conversely, other studies suggested that the blend of EOs and sodium butyrate yielded no significant difference in growth performance [50].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results indicated that feeding with BLJ could positively improve FCR in broilers. Consistent with our findings, several recent studies documented that EOA improved the growth performance and/or feed utilization in broilers [47,48] and turkeys [49]. Conversely, other studies suggested that the blend of EOs and sodium butyrate yielded no significant difference in growth performance [50].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our findings, broilers infected with C. perfringens and treated with combined sodium butyrate and EOs (ginger oil and carvacrol) protected with vegetable fat also yielded better BWG, increased villus lengths and VH/CD ratios and decreased gross pathological and histopathological lesion scores compared with those of the controls [53]. Two previous studies demonstrated that feeding blends of sorbic acid, fumaric acid and thymol to broiler chickens reared under conventional conditions changed the intestinal morphology, resulting in longer villi and a greater VH/ CD ratio [35,47]. In addition, several studies have shown improved gut morphology and decreased gross intestinal lesion scores in NE-infected broiler chickens fed either EO-supplemented [18] or OA-treated diets [28].…”
Section: Discussionmentioning
confidence: 91%
“…Also, Lee et al () evaluated the beneficial effects of organic acids on immune responses against viral antigens (H9N2) in broiler chickens and they found that the CD4 + CD25 + T‐cell percentage was higher in the OV group (diet supplemented with organic acids and administered a H9N2 vaccine [OV]) than in the control, demonstrating the potential induction of regulatory T cells by feed additive. Liu et al () used 450 1‐day‐old Cobb 500 chicks to evaluate the beneficial role of protected organic acids and essential oils mixture product at 0.30 g/kg. Authors pointed out that supplementation of the product improved crypt depth and villus height of the jejunum, and spleen index at 42 days as compared to control ( p < .05).…”
Section: Role Of Acidifiers In Nutritionmentioning
confidence: 99%
“…Enramycin is a polypeptide antibiotic produced by Streptomyces fungicides [3]. Enramycin is one of the most common antibiotics that incorporated in the broilers feed for growth promotion purposes [4].…”
Section: Introductionmentioning
confidence: 99%